2020
DOI: 10.1016/j.heliyon.2020.e04530
|View full text |Cite
|
Sign up to set email alerts
|

Association of prosocial behavior with ever smoking and alcohol drinking among school-going adolescents

Abstract: Background Smoking and consuming alcohol remain hazardous acts to health, which are important to prevent in adolescents. Prosocial behavior has increasingly being noticed to be related with substance use. This study investigated the association between the trying of smoking and alcohol with prosocial behavior among school-going adolescents in Terengganu, Malaysia. Methods This cross-sectional study was conducted among 732 school adolescents aged between 13 and 18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
3
3
2
Order By: Relevance
“…Our results are coherent with previous evidence showing that improvements in self-efficacy are related to reductions in smoking susceptibility 40 , and suggest that higher levels of self-efficacy can reduce the probability of belonging to a group with descriptive social norms favorable towards smoking. Our results were inconclusive regarding the relationship between pro-sociality traits (need to belong, fear of negative evaluation, and pro-sociality) and belonging to any particular smoking social norms groups, even though other studies have shown a negative relationship between pro-sociality traits and smoking susceptibility 41 , 42 and a negative relation between pro-social influence and age 43 .…”
Section: Discussioncontrasting
confidence: 95%
“…Our results are coherent with previous evidence showing that improvements in self-efficacy are related to reductions in smoking susceptibility 40 , and suggest that higher levels of self-efficacy can reduce the probability of belonging to a group with descriptive social norms favorable towards smoking. Our results were inconclusive regarding the relationship between pro-sociality traits (need to belong, fear of negative evaluation, and pro-sociality) and belonging to any particular smoking social norms groups, even though other studies have shown a negative relationship between pro-sociality traits and smoking susceptibility 41 , 42 and a negative relation between pro-social influence and age 43 .…”
Section: Discussioncontrasting
confidence: 95%
“…Our results are coherent with previous evidence showing that improvements in self-e cacy are related to reductions in smoking susceptibility 40 , and suggest that higher levels of self-e cacy can reduce the probability of belonging to a group with descriptive social norms favorable towards smoking. Our results were inconclusive regarding the relationship between the pro-sociality traits (need to belong, fear of negative evaluation, and pro-sociality) and belonging to any particular smoking social norms groups, even though other studies have shown a negative relationship between pro-sociality traits and smoking susceptibility 41,42 and a negative relation between pro-social in uence and age 43 .…”
Section: Discussioncontrasting
confidence: 92%
“…In line with previous studies, our study confirmed that the risk factors of tobacco smoking included male gender [21, 23, 24], mental health problems [25, 26], having sexual intercourse [27], truancy [28, 29], and alcohol consumption [23, 24, 28].…”
Section: Discussionsupporting
confidence: 92%
“…In South-East Asia region, the prevalence of cigarette smoking ranged from 1.2% in India (2007) to 11.7% in Indonesia (2007). Within the Western Pacific region, the prevalence of tobacco use ranged from 3.5% in In line with previous studies, our study confirmed that the risk factors of tobacco smoking included male gender [21,23,24], mental health problems [25,26], having sexual intercourse [27], truancy [28,29], and alcohol consumption [23,24,28].…”
Section: (Insert Table 5 Here) Discussionsupporting
confidence: 91%